Building Cost Estimation Model Based On Cost Significant Elements Of High-Rise Condominium Projects In Klang Valley Malaysia - Lim, Cheng Sim (2022)
In Malaysia, pricing each single item of bills of quantities to predict the cost of construction projects in the detailed design phase is still the most widely used traditional cost estimating technique. However, this technique has become ineffective in accuracy because of its dependency on the level of the project data source and is time-consuming due to the tediousness of pricing large numbers of small work items. Some overseas researchers have developed costsignificant estimation models but there is no such study in Malaysia, not even on construction industry stakeholders’ awareness of this alternative cost estimating technique. Therefore, this research aimed to develop a building cost estimation model based on the cost-significant elements (CSEs) of high-rise condominium projects (HRCPs) to aid building contractors and consultant quantity surveyors (CQSs) to substantially reduce the time and effort spent on cost checking during the tendering period. Three research objectives were set: RO1 to determine the building contractor’s and CQSs’ levels of cost significance awareness of HRCPs in Klang Valley, RO2 to appraise the CSEs of HRCPs in Klang Valley; and RO3 to develop a building cost estimation model based on the CSEs of HRCPs in Klang Valley. In this study, a survey questionnaire was used to achieve RO1 and case studies were used to achieve iii RO2 and RO3. The results showed that the levels of cost significance awareness of HRCPs were low for both building contractors and CQSs. The CSEs were appraised successfully, and the cost-significant model has been successfully developed using six historical projects. The model was tested using two similar projects and achieved an accuracy of 98% to 99%. Since the model has been proven to be accurate, it will be extremely beneficial for use by the local construction industry to vastly reduce the time spent on cost estimation processes during tendering.